P53 Codon 72 Polymorphism의 위암의 예민도 - 허윤정(Youn-Jung Heo); 조현민(Hyeon-Min Cho); 진형민(Hyung-Min Chin); 김욱(Wook Kim); 전해명(Hae-Myung Jeon) (Annals of surgical treatment and research, 2005)
Purpose: The P53 codon 72 polymorphism results in either arginine or proline, there are many studies to clear the relationship between P53 codon 72 genotypes and specific cancer risk and susceptibility. The purpose of this study was to investigate the association of the genotype distribution of the P53 codon 72 polymorphism and gastric cancer susceptibility via in comparison of gastric cancer group and normal control genotypes. We also studied the relation between the distribution of P53 codon 72 genotypes and the state of P53 immunohistochemical staining, infectivity of Helicobacter pylori (H.pylori) and the clinicopathologic findings in gastric cancer patients. Methods: In our study, the samples consisted of 145 gastric cancer patients and 77 normal controls. The analysis was performed by polymerase chain reaction (PCR), restriction fragment length polymorphism (RFLP) method using DNA extracted from gastric cancer patients blood and normal controls blood. Results: The frequency of three genotypes arg/arg, arg/ pro and pro/pro in gastric cancer patients was 41.4%, 38.6% and 20.0%. In controls, it was 36.3%, 53.2% and 10.3%. There was no statistical significance (P=0.312, 0.665). There was no correlation between the frequency of the three genotypes and the state of P53 immunohistochemical staining, infectivity of H. pylori. The pro/pro homozygote was more frequent in lymph node metastasis (25.6% vs 7.3%, P= 0.026). Conclusion: The P53 codon 72 polymorphism does not contribute to gastric cancer susceptibility. The P53 codon 72 polymorphism is not associated with the state of P53 immunohistochemical staining and the infectivity of H. pylori but pro/pro genotype is associated with the lymph node metastasis in gastric cancer patients. (J Korean Surg Soc 2005; 69:24-30) KCI Citation Count: 1